Aplikasi Absensi Siswa Berbasiskan Android - Christina, Sherly; Oktaviyani, Enny Dwi; Ronaldo, Deddy; Zaini, Rosya M (Jurnal ELTIKOM : Jurnal Teknik Elektro, Teknologi Informasi dan Komputer, 2019)
The recording of student attendance aims to monitor the student attendance quantity and educate students to be disciplined. Student attendance records that are currently done manually on the paper can be improved to increase the quality of the attendance data processing, service quality and system in the School. This study aims to build an Attendance application based on Android platform that can be used on the teacher's mobile device. Waterfall is the method which is used to develop the attendance application in this study. Then, to ensure the application performance, the attendance application will be tested by the blackbox testing method. The test results using the blackbox testing show that the features in the attendance application perform according to its purpose. This attendance application can facilitate the homeroom teacher to carry out the student attendance recording process daily and to create the student attendance data recapitulation.